Avebury, Großbritannien: Landschaftsarchäologische Betrachtungen - Darvill, Timothy; Lüth, Friedrich (e-Forschungsberichte des DAI, 2023)
Large parts within the prehistoric landscape-complex „Stonehenge-Avebury“ are protected and the complex belongs to one of the earlier inscriptions on UNESCO´s World Heritage List. The prehistoric landscapes have been in the focus of historic research for more than 250 years; University of Bournemouth, National Trust, English Heritage (now Historic England) and the German Archaeological Institute (DAI) agreed upon a survey programme in 2007 to investigate the area between the monuments on both parts of the WHS. In Avebury the multi-channel-magnetometry has revealed deep insights into the landscape between the monuments. While some areas remain free from new indicators, other parts of the complex contain much more remains than previous surveys and research work have been able to detect, not only between the known monuments but also, as the example of Windmill Hill shows, within the historic complex. Cold-War intrusions disturbed parts of a barrow group and one of the “barrows” happens to be identified as base for a windmill. Remains from Roman, Saxon and mediaeval periods south of Waden Hill join up with the modern village of Avebury. In 2016 and 2017 surveys in the vicinity of the monuments will deliver sufficient data that are statistically relevant for further research.